HIGHER ORDER THINKING SKILLS (HOTS) SEBAGAI PREDIKTOR KETERGANTUNGAN PENGGUNAAN ARTIFICIAL INTELLEGENCE (AI) PADA MAHASISWA PPKN - Agustin, Gisela; Aditya Candra, Alif; Dewi, Nurmalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of Artificial Intelligence (AI) among students is increasingly massive, potentially leading to excessive dependence if not balanced with critical thinking skills. Based on initial observations at the University of Jambi, Pancasila and Citizenship Education Study Program, class of 2025, as many as 65.71% of students are in the high AI dependence category. This study aims to analyze the effect of HOTS on the dependence on AI use in these students. The method used is a quantitative approach with an associative type and an ex-post facto method. The study population was 108 students and samples were taken saturated. The data collection instrument was a 4-point Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out through simple linear regression analysis with the help of SPSS Version 26. The results showed that HOTS had a positive and significant effect on dependence on AI use, evidenced by the calculated t_value (15.059) > t_table (1.983) and a significance value of 0.000 < 0.05. The magnitude of HOTS' influence on AI reliance reached 68.1% (R2 = 0.681), while the remaining 31.9% was influenced by factors outside this study. This finding indicates that students with higher order thinking skills tend to use AI more intensively due to the complex cognitive demands.